A simple and rapid method for isolation of DNA for molecular markers and transgene analysis in safflower: SIMPLE AND RAPID METHOD FOR ISOLATION OF DNA FOR MOLECULAR MARKERS IN SAFFLOWER - BISHUN DEO PRASAD; SANGITA SAHNI; PANKAJ KUMAR (Journal of Oilseeds Research, 2018)
In spite of the possibility of analysing large samples and the rapidity of Polymerase Chain Reaction (PCR) technology, the usual protocols for DNA plant extraction remain time-consuming, slow and involves use of hazardous chemicals. To lessen labor, time or cost of DNA extraction, a simple and instant method for genomic DNA extraction from leaf tissue of safflower (Carthamus tinctorius L.) leaf is established. Small quantity of tissue material (typically3-5mg) was ground in a centrifuge tube using plastic pestle in extraction solution. ExtractedDNA was suitable for PCR analysis, without centrifugation. The feasibility of this method was confirmed by testing molecular markers and transgene detection. This method requires less than 1 mg of plant tissue stored frozen or used fresh and is useful for molecular marker analyses as well as transgene detection.